2019
DOI: 10.1111/1759-7714.13259
|View full text |Cite
|
Sign up to set email alerts
|

Sequential ALK inhibitor treatment benefits patient with leptomeningeal metastasis harboring non‐EML4‐ALK rearrangements detected from cerebrospinal fluid: A case report

Abstract: A 47‐year‐old female with ALK‐rearranged lung adenocarcinoma developed leptomeningeal metastasis (LM) after progression on first‐line crizotinib. Alectinib 300 mg was commenced and the patient achieved clinical and radiographic improvements. After nine months of alectinib 300 mg, she started to experience symptomatic LM. Two concurrent non‐EML4‐ALK rearrangements, LOC388942‐ALK and LINC00211‐ALK, were identified from the CSF but not from the plasma samples. With the primary lung lesions remaining stable, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…3,[5][6][7][8][9][10][11] With the development of gene-sequencing technologies, more non-EML4-ALK fusions are being identified, with their responses to crizotinib reported in several case reports. [12][13][14][15] Crizotinib is the first tyrosine kinase inhibitor approved by the US Food and Drug Administration in 2011 for ALK-rearranged NSCLCs, and its efficacy has been comprehensively verified in a series of clinical trials. 16,17 Despite dramatic responses to crizotinib therapy, the response duration of patients treated with crizotinib varies and emerging data suggest that the EML4-ALK breakpoint variants or ALK fusion partners affect clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…3,[5][6][7][8][9][10][11] With the development of gene-sequencing technologies, more non-EML4-ALK fusions are being identified, with their responses to crizotinib reported in several case reports. [12][13][14][15] Crizotinib is the first tyrosine kinase inhibitor approved by the US Food and Drug Administration in 2011 for ALK-rearranged NSCLCs, and its efficacy has been comprehensively verified in a series of clinical trials. 16,17 Despite dramatic responses to crizotinib therapy, the response duration of patients treated with crizotinib varies and emerging data suggest that the EML4-ALK breakpoint variants or ALK fusion partners affect clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of a German early access program revealed a partial response rate of 77.8% among 9 patients with LM, but did not provide further details regarding duration of response [90]. While these expanded access datasets are limited due to their retrospective nature and lack of protocolized neuraxial assessments, they complement a number of case reports demonstrating improvement of both LM disease burden and neurologic symptoms following lorlatinib treatment [91][92][93].…”
Section: Met Genomic Alterations In Nsclcmentioning
confidence: 99%
“…CSF sampling of 10 total patients treated with lorlatinib 100 mg daily in phase I/II studies revealed a CSF-to-plasma ratio of 0.73 [92] and 0.77 [93], far higher than what had been previously demonstrated for crizotinib. Prospective studies of lorlatinib in patients with LM are lacking, however a phase II subgroup analysis and several case reports in patients with ALK+ LM have highlighted rapid symptom improvement and long-lasting intracranial responses, ranging 8-22 months [88,[94][95][96]. The largest cohort analysis of leptomeningeal activity of lorlatinib derives from an international early/expanded access program of 95 previously TKI-treated patients, in which 11 evaluable patients with LM (9 ALK+ and 2 ROS1+) achieved an intracranial ORR of 45% (95% CI 17-77) and DCR of 91% (95% CI 59-100) [97].…”
Section: Alk Inhibitorsmentioning
confidence: 99%